Investment, Uncertainty and Expectations - Egerton, R. A. D. (Review of Economic Studies, 1954)
Journal Article Investment, Uncertainty and Expectations Get access R. A. D. Egerton R. A. D. Egerton Belfast Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 22, Issue 2, 1954, Pages 143–150, https://doi.org/10.2307/2296288 Published: 01 January 1954